Equidad organizacional y gestión administrativa de la Universidad Técnica de Machala. - Mora Quevedo, Maura Soraya (My University, 2021)
The objective of this work is to carry out a theoretical journey on organizational equity and its relationship with administrative management and determine what impact it has on the Technical University of Machala in its three dimensions: distributive, procedural and interactional justice, carried out through a study in two university levels, teachers and employees. The research results determined that the perceptions of organizational justice of human talent in each of the phases of administrative management differ, since in some cases the statistical verification corroborated the fact that the perception of the teachers was favorable, on the other hand for the staff administratively, this perception was lower.
El objetivo de este trabajo es realizar un recorrido teórico sobre la equidad organizacional y su relación con la gestión administrativa y determinar qué incidencia tiene en la Universidad Técnica de Machala en sus tres dimensiones: justicia distributiva, procedimental e interaccional, realizadas a través de un estudio en dos estamentos universitarios, los docentes y empleados. Los resultados investigativos determinaron que las percepciones de justicia organizacional del talento humano en cada una de las fases de la gestión administrativa difieren, pues en algunos casos la comprobación estadística corroboró el hecho de que la percepción de los docentes era favorable, en cambio para el personal administrativo esta percepción era menor.
Keywords: JUSTICIA ORGANIZACIONAL; ECUADOR